2020
DOI: 10.1194/jlr.ra119000606
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry imaging and LC/MS reveal decreased cerebellar phosphoinositides in Niemann-Pick type C1-null mice

Abstract: Niemann-Pick disease type C1 (NPC1) is a lipid storage disorder in which cholesterol and glycosphingolipids accumulate in late endosomal/lysosomal compartments because of mutations in the NPC1 gene. A hallmark of NPC1 is progressive neurodegeneration of the cerebellum as well as visceral organ damage; however, the mechanisms driving this disease pathology are not fully understood. Phosphoinositides are phospholipids that play distinct roles in signal transduction and vesicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Specifically, a recent study using 2D MALDI-MSI indicated decreases in PIP and PIP 2 in the cerebellum of the NPC1-null mice, providing evidence for the alteration of PI downstream metabolites in the NPC1 disease. 40 Besides, some other reports observed changes in protein kinase C and phosphatidylinositol-3 kinase expression in the NPC1 animals. 41,42 Our findings of increases of PI and LPI combined with decreases of its downstream metabolites in previous reports indicated that some kinases in the phosphoinositide synthesis pathway might be impaired.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Specifically, a recent study using 2D MALDI-MSI indicated decreases in PIP and PIP 2 in the cerebellum of the NPC1-null mice, providing evidence for the alteration of PI downstream metabolites in the NPC1 disease. 40 Besides, some other reports observed changes in protein kinase C and phosphatidylinositol-3 kinase expression in the NPC1 animals. 41,42 Our findings of increases of PI and LPI combined with decreases of its downstream metabolites in previous reports indicated that some kinases in the phosphoinositide synthesis pathway might be impaired.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Phosphorylation of K V 2.1 by CDK5 enhances channel clustering 67 . Furthermore, CDK5 kinase activity is elevated in NPC disease 68 , 90 . We find that CDK5 activators, p35/p39 have increased expression in NPC disease and inhibition of CDK5 kinase activity with roscovitine abrogates enhancement of both K V 2.1 and Ca V 1.2 clustering in the PM of NPC neurons.…”
Section: Discussionmentioning
confidence: 99%
“…PtdIns-4,5-P 2 plays crucial roles in neurons, including vesicle docking at the plasma membrane during endocytosis at the synapse, coupling exo- and endocytosis and regulating actin assembly . Phosphoinositides, in particular PtdIns-4,5-P 2 , are significantly depleted in the NPC1-disease neurons, leading to hyperexcitability. , It has also been recently reported than NPC1 regulated the distribution of phosphatidylinositol-4 kinases at lysosome and Golgi membranes . Although the expression level of Synj1 in NPC1 I1061T fibroblasts is reportedly not significantly changed, the implication of Synj1 in hyperexcitability through modification of PtdIns-4,5-P 2 cannot yet be ruled out …”
Section: Resultsmentioning
confidence: 96%